A flux pumping method applied to the magnetization of YBCO superconducting coils: frequency, amplitude and waveform characteristics. (22nd February 2016) - Fu, Lin; Matsuda, Koichi; Lecrevisse, Thibault; Iwasa, Yukikazu; Coombs, Tim
Abstract: This letter presents a flux pumping method and the results gained when it was used to magnetize a range of different YBCO coils. The pumping device consists of an iron magnetic circuit with eight copper coils which apply a traveling magnetic field to the superconductor. The copper poles are arranged vertically with an air gap length of 1 mm and the iron cores are made of laminated electric steel plates to minimize eddy-current losses. We have used this arrangement to investigate the best possible pumping result when parameters such as frequency, amplitude and waveform are varied. We have successfully pumped current into the superconducting coil up to a value of 90% of I c and achieved a resultant magnetic field of 1.5 T.